Organic and isotopic geochemistry of source-rocks and crude oils from the East Sirte Basin (Libya) - Aboglila, Salem Abdulghni-O (Curtin University, 2010)
The Sirte Basin is a major oil producing area in Libya, but the understanding of the processes that have led to the petroleum accumulation is still limited. Exploration studies of this area have shown that the oils are mixtures of several charges and may be from different source rocks. The main aims of this thesis are to improve our understanding of the petroleum accumulation history in the East Sirte Basin.Biomarker ratios, together with stable carbon (δ[superscript]1[superscript]3C) and hydrogen (δD) isotopic compositions of individual hydrocarbons have been applied to 24 crude oils from the East Sirte Basin to delineate their sources and respective thermal maturities. The crude oil samples are divided into two main families (A and B) based on differences in source inputs and thermal maturity. Using source-specific biomarker parameters based on pristane/phytane (Pr/Ph), hopane/sterane ratios, dibenzothiophene (DBT) / phenanthrene (P), Pr/n-C[subscript]1[subscript]7, Ph/n-C[subscript]l[subscript]8 and the distribution of tricyclic and tetracyclic terpanes, family B oils are ascribed a marine source rock deposited under sub-oxic conditions, whereas family A oils have a more terrestrial source affinity. This source classification is supported by the stable carbon isotopic compositions (δ[superscript]1[superscript]3C) of the n-alkanes. Family A oils were found to be more mature based on differences between the stable hydrogen isotopic compositions (δD) of Pr and Ph and the n-alkanes, as well as the δ[superscript]1[superscript]3C values of n-alkanes.Within a complex geological setting several potential source rocks have been recognised, ranging in age from Precambrian to Eocene. Biomarker ratios, together with δ[superscript]1[superscript]3C and δD of individual hydrocarbons have been applied to 21 source rock extracts from the East Sirte Basin to establish their respective thermal maturity and palaeoenvironmental conditions of deposition. Rock Eval pyrolysis data obtained from the source rocks of the Sirte, Tagrifet, Rakb, Rachmat, Bahi and Nubian Formations show that the organic matter (OM) is mainly dominated by a Type II/III kerogen. Vitrinite reflectance (% R[subscript]o range: 0.46 – 1.38) data support variations in thermal maturity and indicate mature to post mature rocks of Sirte and Rachmat Formations and early to mid stage maturities for the rest of the formations. The Sirte Formation in the studied area was found to be relatively more thermally mature than the Tagrifet, Rakb, Rachmat, Bahi, and Nubian Formations, reflected by δD of Pr and Ph (less depleted in D).Various unusual steroid biomarkers in the oils and East Sirte source-rocks were identified by gas chromatography- mass spectrometry (GC-MS) and GC- metastable reaction monitoring (MRM) mass spectrometry. These included 24-norcholestanes, dinosteranes, 4α-methyl-24-ethylcholestanes and triaromatic steroids. Diatoms, dinoflagellates and/or their direct ancestors are the proposed sources of these components. These biomarker parameters have been used to establish a Mesozoic oil-source correlation of the East Sirte Basin. This is consistent with the presence of dinoflagellate cysts in the Nubian Formation of Lower Cretaceous age.